Analisis dan Segmentasi Pasar Mobil Bekas di Jabodetabek Berdasarkan Data Iklan OLX Menggunakan Metode K-Means Clustering dan Dashboard Business Intelligence - Dio Faturamdani; Dedi Trisnawarman (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The development of information technology and the internet has increased the use of online marketplaces as sources of transaction and information, including in the used vehicle sector. OLX provides vehicle information such as price, brand, year, fuel type, mileage, and seller location, but the data is presented individually, making overall market analysis difficult. This study aims to design a used car market analysis dashboard based on OLX advertisement data in the Greater Jakarta area using a Business Intelligence (BI) approach. Data were collected through web scraping and processed through data cleaning to improve quality. Market segmentation was conducted using the K-Means Clustering method based on vehicle price, year, and mileage. A Star Schema analytical database was implemented to support data management and visualization. User information needs were identified through questionnaires to determine Measures and Key Performance Indicators (KPIs). The dashboard was developed using Microsoft Power BI and features interactive visualizations, including KPI Cards, Bar Charts, Line Charts, and Pie Charts. Results show that the dashboard presents market information in a structured and informative manner, including vehicle counts, average prices, market trends, brand and location distributions, and segmentation results. Black Box Testing confirmed that all dashboard functions operated as expected, supporting faster and more effective data-driven decision making.